2022
DOI: 10.1097/adm.0000000000000948
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations to Opioid Use Disorder Care During the COVID-19 Pandemic: A National Survey of Prescribers

Abstract: Objectives: Among opioid use disorder (OUD)-treating providers, to characterize adaptations used to provide medications for OUD (MOUD) and factors associated with desire to continue virtual visits post-COVID-19 pandemic. Methods: In a national electronic survey of OUD-treating prescribers (July-August 2020), analyses restricted to X-waivered buprenorphine prescribers providing outpatient, longitudinal care for adults with OUD, quantitative and qualitative analyses of survey items and free text responses were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(39 citation statements)
references
References 25 publications
3
36
0
Order By: Relevance
“…29 Other surveys and interviews of providers similarly found significant uptake of telehealth for buprenorphine among prescribers. 27,28,30,31 Trends in uptake of telehealth varied across different types of programs offering buprenorphine: A survey of 57 primary care practices found that 92.3% were conducting initiation visits via telehealth, 32 and a survey of 325 syringe service programs (SSPs) found that a quarter were initiating buprenorphine via telehealth. 33 In a survey of OTP directors in Pennsylvania, 40% (8) offered video appointments and 50% (10) offered telephone appointments for buprenorphine follow-up visits, but only 25% (5) and 10% (2) respectively did so for initiation.…”
Section: Uptake Of Telehealth Buprenorphinementioning
confidence: 99%
See 3 more Smart Citations
“…29 Other surveys and interviews of providers similarly found significant uptake of telehealth for buprenorphine among prescribers. 27,28,30,31 Trends in uptake of telehealth varied across different types of programs offering buprenorphine: A survey of 57 primary care practices found that 92.3% were conducting initiation visits via telehealth, 32 and a survey of 325 syringe service programs (SSPs) found that a quarter were initiating buprenorphine via telehealth. 33 In a survey of OTP directors in Pennsylvania, 40% (8) offered video appointments and 50% (10) offered telephone appointments for buprenorphine follow-up visits, but only 25% (5) and 10% (2) respectively did so for initiation.…”
Section: Uptake Of Telehealth Buprenorphinementioning
confidence: 99%
“…37,38 Others offered patients the option to access remote technologies from a clinic to communicate with a prescriber if they did not have access to personal technologies for telehealth visits. 50 Others shifted psychosocial services to virtual platforms, 51 discontinued or required less frequent drug screening, 28,29,32,37,41,51,52 or required less frequent psychosocial service utilization. 29,51 Some practices offered longer days-supply to reduce burden, 29,32,37,51 while others offered shorter days-supply to encourage more frequent checkins.…”
Section: Practice Modifications To Support Telehealthmentioning
confidence: 99%
See 2 more Smart Citations
“…Authors concluded that SUD treatment via telehealth is promising, but must be studied further. 14 In the context of this sudden shift in modality, as well as early indications that providers working in SUD treatment settings may prefer to continue to offer telemedicine after the effects of the pandemic decrease, 15 it is imperative to examine how use of telehealth affects treatment engagement and outcome. 1 A survey of SUD treatment providers indicated that video was considered to be the preferred telehealth method, though telephone was considered to be more accessible.…”
Section: Introductionmentioning
confidence: 99%